Governance, ownership and performance of government-linked and non-government companies: a comparative study of public listed companies in Malaysia, India and Singapore - D. Sundarasen, Sheela Devi; Rahman, Muhammad Sabbir; Nakiran, Rajangam (Medwell Journals, 2014)
This paper aims to examine the extent to which corporate governance and ownership of Government-Linked Corporations (GLCs), and non- Government-Linked Corporations affect the profitability, liquidity and gearing of Malaysian, Indian and Singaporean companies for the period 2010 – 2012. In auxiliary, this research also scrutinizes the degree of similarities and divergences from the above mentioned relationships among the Malaysian, Indian and Singaporean companies. This research used two thousand and forty eight listed companies from Malaysia, two thousand four hundred and sixty listed companies from India and one thousand three hundred and fifty six listed companies in Singapore for the period 2010 to 2012. The results designate differences in the relationship between board structure and ownership structure on the profitability, liquidity and gearing of government-linked and non-government-linked companies in Malaysia, India and Singapore. Malaysia and India share similarities in most relationships but the adverse for Singapore. It is conjectured that governance and its proper execution needs to be seriously considered by policy makers to further improve investor confidence and ensure sustainability.